The effect of sandblasting versus acid etching on the surface roughness and biaxial flexural strength of CAD/CAM resin-matrix ceramics (In vitro study) - Heba A. Muhammed; Elsayed M. Mahmoud; Amal E. Fahmy; Dina M. Nasr (BMC, 2023)
Abstract Background CAD/CAM resin matrix ceramics are one of the materials used in dental offices. The long-term success of the restoration depends on the bond strength of the restoration to the tooth and other materials; thus, surface treatment of the restoration is necessary to achieve this. But such treatment may affect the restoration strength. The purpose of this study is to assess the impact of various surface treatments on the surface roughness (Ra) and the biaxial flexural strength of two CAD-CAM resin-matrix ceramics. Methods Thirty-six-disc-shaped specimens, each measuring 1.2 mm in thickness and 12 mm in diameter, were machined from two resin-matrix ceramic blocks (Lava Ultimate and Cerasmart) (n = 18). Based on the surface treatments, each material was divided into 3 groups: control (no treatment), 50-μm Al2O3 sandblasting, or 9% hydrofluoric acid etching (n = 6). The surface roughness (Ra) was evaluated by the 3D laser scanning microscope. Then, specimens were aged by thermal cycling (5000 cycles) and tested for biaxial flexural strength using a universal testing machine at a crosshead speed of 1.0 mm/min. Results No significant differences in flexural strength or Ra were found for Lava Ultimate among the surface treatment groups. For Cerasmart, only the sandblasting group showed significantly higher Ra values than the control group. Also, the Ra values for the sandblasting group were significantly higher than those for the acid etching group. The flexural strengths of the sandblasting and acid etching groups for Cerasmart were statistically similar, and both were significantly lower than the control group. Conclusions Although all of the applied surface conditioning techniques improved Ra, they had a negative impact on the flexural strength of resin-matrix ceramics. Thus, clinicians should utilize the appropriate surface treatment techniques, taking into account their effects on the surface roughness and mechanical properties of resin-matrix ceramics.